Nothing Tastes as Good as Thin Feels: Low Positive Emotion Differentiation and Weight-Loss Activities in Anorexia Nervosa. (July 2014) - Selby, Edward A.; Wonderlich, Stephen A.; Crosby, Ross D.; Engel, Scott G.; Panza, Emily; Mitchell, James E.; Crow, Scott J.; Peterson, Carol B.; Le Grange, Daniel
Positive emotion (PE) has not been well studied in anorexia nervosa. Low positive emotion differentiation (PED), which involves a diminished ability to distinguish between discrete PEs, may contribute to PE dysregulation in anorexia. Specifically, low PED may interact with elevated PE intensity to both motivate and reinforce weight-loss and evaluation behaviors. Using ecological momentary assessment, we examined PE and weight-loss behaviors reported during a 2-week period. As hypothesized, low PED predicted more vomiting, laxative use, exercising, weighing, checking for fat, and restricting. Furthermore, participants with low PED who experienced elevated average PE intensity reported even more frequent behaviors. Within-subjects analyses indicated that for participants with low PED, more weight-loss behaviors at one recording predicted elevated PE at the subsequent recording. Similarly, for participants with low PED, higher momentary PE predicted more subsequent weight-loss behaviors. Thus, low PED in anorexia may reinforce and motivate weight-loss behavior.